Characteristics of Urinary Tract Stone Patients in Central Sulawesi, 2020–2024 - Firmansyah SY. Labanu; Aristo Aristo (International Journal Of Health Science, 2025)
Urolithiasis is a common urologic disorder characterized by stone formation along the urinary tract, predominantly affecting adult males and showing a high recurrence rate. Despite numerous global studies, data on the Central Sulawesi population remain limited, hindering the development of local management strategies. This study aims to describe the epidemiological and clinical characteristics of patients with urinary tract stones in Central Sulawesi from 2020 to 2024. A retrospective cross-sectional study was conducted using secondary data from electronic medical records and surgical archives of referral hospitals. A total of 4,078 patients diagnosed with urinary tract stones were analyzed descriptively based on age, sex, diagnosis, and treatment modalities. The mean age was 47.77 ± 14.80 years, and males accounted for 53.4% of cases. Ureteral stones were the most frequent diagnosis (48.4%), followed by renal stones (40.4%) and bladder stones (11.0%). In terms of management, ureterorenoscopy (URS) with DJ stent insertion was most common (20.15%), followed by extracorporeal shock wave lithotripsy (ESWL) (10.15%), while 47.29% were managed with medical expulsive therapy (MET). These findings indicate that urolithiasis in Central Sulawesi mainly affects males in productive age, with ureteral stones as the leading type. Minimally invasive procedures, especially URS and ESWL, dominate clinical practice, highlighting the need for strengthened prevention, early detection, and urological service infrastructure.